Directions of Changes in the Functioning of Economic Instruments for Environmental Policy in Poland - Ptak, Michał (Equilibrium. Equilibrium. Quarterly Journal of Economics and Economic Policy, 2010)
Environmental policy instruments allow incorporating the problem of using the natural resources into the decision-making process of individual agents. One of the most efficient instruments for environmental protection are economic instruments, the indirect methods of influencing agents’ behaviour. The aim of the article is to present the state of the Polish system of economic instruments in the light of other European countries’ experiences (especially the European Union countries) and prospects for the use of economic instruments in the environmental policy during the oncoming years. The study is based on a subject literature review, reports ordered by the Polish Ministry of Environment and publications published by The Organisation for Economic Co-operation and Development (OECD) and the European Environment Agency (EEA). The analysis suggests that economic instruments are widely used in the Polish environmental policy. The main economic instruments in this policy are environmental charges and fines. Some of these charges and fines have been used in the Polish environmental policy for several dozen years. Revenues from these instruments are earmarked for environmental expenditures. There are also some new, interesting economic instruments applied in the Polish environmental policy, such as: deposit-refund systems, tradable energy certificates and emissions trading scheme. There are some opportunities for expanding the use of economic instruments for the environmental policy in Poland. For example, there could be increased the use of some environmental charges or taxes, and the environmental insurance. Poland could also implement an environmental tax reform.